Changes in citizens’ anxiety, depression, and PTSD after the Seoul Halloween crowd crush in 2022 - Yun-Jung Choi; Heewon Song (Scientific Reports)
Abstract This study aims to understand the mental health of South Koreans one year after the Seoul Halloween crowd disaster(hereafter referred to as the Seoul Halloween disaster), an anthropogenic disaster that occurred in 2022. In total, 651 participants completed three online surveys to measure anxiety, depression, and post-traumatic stress disorder (PTSD) over a year after the disaster. The collected data were then analyzed with descriptive statistics, repeated-measures analysis of variance (ANOVA), and independent samples t-tests using the SPSS 28 program. Six months after the Seoul Halloween disaster, the mean mental health scores, including those for anxiety, depression, and PTSD, were all above the cutoff point, and these results continued without significant change over the year. Mainly, for PTSD, the high-risk group consistently accounted for more than 30% of the subjects, with a mean score of 39, which is considerably above the cutoff of 25 for high risk. In addition, changes in alcohol consumption and intentionally avoiding the affected area had higher anxiety, depression, and PTSD. Therefore, there is a need to target a broader range of people for post-disaster psychological support and provide resources to prevent psychological trauma from becoming chronic with a medium- to long-term approach.